2014
DOI: 10.15698/mic2014.09.165
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular calcium triggers unique transcriptional programs and modulates staurosporine-induced cell death in Neurospora crassa

Abstract: Alterations in the intracellular levels of calcium are a common response to cell death stimuli in animals and fungi and, particularly, in the Neurospora crassa response to staurosporine. We highlight the importance of the extracellular availability of Ca2+ for this response. Limitation of the ion in the culture medium further sensitizes cells to the drug and results in increased accumulation of reactive oxygen species (ROS). Conversely, an approximately 30-fold excess of external Ca2+ leads to increased drug t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Ca 2+ is also involved in the increasing threshold of N. crassa to antifungals such as staurosporine. 44 Calcium plays a role in the mechanisms of plasma membrane remodeling in S. cerevisiae budding 45 and during cell fusion in N. crassa . 14,17 In this work, we report NCU10610 (Ca 2+ regulator with fig 1 domain) significantly repressed by chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ is also involved in the increasing threshold of N. crassa to antifungals such as staurosporine. 44 Calcium plays a role in the mechanisms of plasma membrane remodeling in S. cerevisiae budding 45 and during cell fusion in N. crassa . 14,17 In this work, we report NCU10610 (Ca 2+ regulator with fig 1 domain) significantly repressed by chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipase C seems to be a pivotal player coordinating recruitment of Ca 2+ to the cytosol during staurosporine-induced cell death as cells lacking the phospolipase C gene plc-2 exhibit increased survival and a staurosporine-induced cytosolic Ca 2+ signature is abolished (Goncalves et al, 2014a ). The importance of extracellular Ca 2+ during staurosporine-induced fungal PCD is supported by the observation that cell death in N. crassa is exacerbated in Ca 2+ -free medium and inhibited when excess Ca 2+ is present (Gonçalves et al, 2014 ). Consistent with these observations, a similar protection from fungal PCD was observed by the presence of an excessive amount of extracellular Ca 2+ in occidiofungin-treated S. cerevisiae cells and chitosan-treated N. crassa cells (Lopez-Moya et al, 2016 ; Robinson et al, 2017 ).…”
Section: Molecular Mediators Of Regulated Cell Deathmentioning
confidence: 96%
“…These observations prompted us to examine the transcriptional profile of N. crassa germlings grown in the absence of calcium in the external medium (http://www.ncbi.nlm.nih.gov/geo/; series record: GSE53013) (24). We narrowed our search to genes that showed decreased expression levels in the absence of calcium and encoded proteins containing transmembrane domains; 50 genes were identified that met these criteria (see Table S1 in the supplemental material).…”
Section: Identification Of New Genes Involved In Germling Fusionmentioning
confidence: 99%
“…Our strategy relied on the identification of genes encoding predicted transmembrane proteins and which showed a significant decrease in expression level in the absence of extracellular calcium (24). We screened 29 strains carrying deletions of candidate genes for defects in membrane merger and cell lysis during germling fusion.…”
mentioning
confidence: 99%